PROBLEMS OF APPOINTING ACTING REGIONAL HEADS FOLLOWING THE POSTPONEMENT OF SIMULTANEOUS ELECTIONS - Muslikhah, Umi; Izzati, Halimah Nur; Hajri, Wira Atma; Abadi, Husnu (JCH (Jurnal Cendekia Hukum), 2023)
The appointment of an official head in the area, as regulated in the provisions above, gives rise to polemics at the level of implementation. Some of the polemics that arise as a consequence of appointing an official head area, among other things, is the lack of transparency in the appointment process of the official head area, and the appointment of an active TNI member as an acting head disfigures the spirit of reform. Additionally, there is not yet a rule managing the executor mechanism for the appointment of the official head area.This study aims to analyze the appointment process of the existing head area position at this moment as an effort to guard popular sovereignty, ensuring it is not injured by inadequate mechanisms, transparent, and yet firm policies that arrange the mechanism for appointing the official head area to prevent conflicts of interest. This study is a normative legal study, where the search uses secondary data with material references. The result of this study is the arrangement of the mechanism for appointing the current Regional Head acting is not yet arranged systematically, so the appointment process of the acting Regional Head experiences several problems, including the existence of a conflict of interest in appointing the acting Regional Head, and the duration of appointing the Acting Regional Heads, who have been around for quite a long time, has implications for the governance of the government area. Additionally, there exists the appointment of acting Regional Heads who are active TNI soldiers.